2012
DOI: 10.1136/acupmed-2011-010069
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Difference between the Effects of One-Point and Three-Point Indirect Moxibustion Stimulation on Skin Temperature Changes of the Posterior Trunk Surface?

Abstract: Objective To determine whether any difference exists in responses to indirect moxibustion relative to thermal stimulation sites. Methods Twenty one healthy men of mean±SD age 22.5±6.1 years were randomly divided into two groups, one receiving a single moxibustion stimulation in three locations (the three-point stimulation group, n=10 participants) and the other receiving three stimulations in one location (the one-point stimulation group, n=11 participants). The thermal stimulation sites were GV14, GV9 and GV4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Previously, thermal stimulation applied to the skin has yielded an increase in local skin temperature and bloodflow volume [1][2][3] . Mori et al [2] reported that localized moxibustion stimulation to the cervical region (at the GV14 acupuncture point, located between the C7 and T1 spinous processes) increased skin temperature on the lower back; however, no differences manifested in the temperature curves and maximum temperatures with the use of two different thermal durations of indirect moxibustion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, thermal stimulation applied to the skin has yielded an increase in local skin temperature and bloodflow volume [1][2][3] . Mori et al [2] reported that localized moxibustion stimulation to the cervical region (at the GV14 acupuncture point, located between the C7 and T1 spinous processes) increased skin temperature on the lower back; however, no differences manifested in the temperature curves and maximum temperatures with the use of two different thermal durations of indirect moxibustion.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Mori et al [2] compared indirect moxibustion applied to one location with indirect moxibustion applied to three locations, with the same duration of stimulation time. Their results showed that administrating moxibustion on three sites produced greater skin-temperature changes compared to the single-site application of moxibustion [3] . The result was similar to that of the current study, which showed a greater temperature response with three-site thermal stimulation with hot stones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 20 A study by Adriaensen et al 21 showed that thermal stimulation of human skin at 44.5–46.5°C activated A-fibre mechano-heat-sensitive nociceptors. Mori et al 22 23 showed that the maximum temperature for indirect moxibustion was approximately 50°C.…”
Section: Introductionmentioning
confidence: 99%